Bornlisy Attenuates Colitis-Associated Colorectal Cancer via Inhibiting GPR43-Mediated Glycolysis - Lu, Xia; Qiao, Shuping; Peng, Chen; Yan, Wenyue; Xu, Zhen; Qu, Junxing; Hou, Yayi; Zhao, Shuli; Chen, Ping; Wang, Tingting (Frontiers in Nutrition, 2021)
There is evidence that probiotics have a broad antitumor effect in colorectal cancer. However, the mechanism remains obscure. Here, we investigated the effect of Bornlisy (BO)-cocktails of three probiotics on colitis-associated colon cancer (CAC) and the underlying mechanism. Treatment of CAC mice with BO resulted in decreased tumor loads as compared to their counterparts. BO also inhibited proliferation and metastasis of CRC cells in vitro. Furthermore, BO inhibited cell proliferation through down-regulating glycolysis. Activating glycolysis reversed the protective role of BO in CAC mice. Mechanically, BO administration promoted the activation of GPR43, followed by its downstream PLC-PKC-ERK pathway, which led to decreased glucose metabolism. These results suggest BO may provide an intervention strategy for CRC therapy, while GPR43 is a potential targeting receptor during BO treatment.